Recombinant Adenovirus Expressing Anti-Cancer Gene in Colon Cancer Cell Explant in Mice - Tan, Seok Shin (2010)
Gene therapy is an alternative method to cure or slow down the progression of malignant cancer. Recombinant adenovirus encoding viral protein 2 (VP2) (ADV-VP2) of very virulent infectious bursal disease virus (vvIBDV) was employed to eliminate cancer cells by apoptosis mechanism. Besides, another recombinant adenovirus encoding murine endostatin (ADV-endo) was constructed aiming to block the formation of new blood vessels that supply nutrients to tumor. Recombinant adenoviruses were found to express the VP2 gene at a significantly high level in cancer cells, especially adenocarcinomas, with the relative quantification (RQ) value from 149.58 to 233.12 fold 72 hour (hr) post-infection (p.i). However, only small traces of VP2 gene expression was found in non-cancer cells, with the RQ value ranging from 0.04 to 0.54 fold 72 hr p.i. The capacity of recombinant adenovirus to infect target cells is dependent on the level of coxsackievirus adenovirus receptor (CAR) available in each cell. DNA fragmentation test, TUNEL assay, FITC Annexin V/PI double staining quantification test and caspase tests were carried out to determine the apoptosis induction level by recombinant adenovirus as well as the apoptosis related pathway. All four apoptosis tests were in agreement with recombinant adenovirus induced apoptosis in cancer cells, particularly in MCF-7, CT26 and HepG2, but not in non-cancer cells. CT26 cells demonstrated DNA fragmentation as early as 24 hr p.i, followed by MCF-7 and HepG2 cells, which showed DNA fragments during 48 and 72 hr p.i. These three cancer cells indicated significantly higher apoptotic cells proportion via TUNEL assay and FITC Annexin V/PI double staining test, with the percentage of apoptotic cells ranging from 78.0% to 60.0%. Caspase tests indicated that recombinant adenovirus activated apoptosis at the late stage of infection, through the intrinsic pathway by caspase 2 (initiator caspase), then led to the activation caspase 3 (effector caspase). No apoptosis was detected in cancer cells infected with mock adenovirus vector, thus apoptosis induction was solely contributed by the inserted gene. Colon cancer cells explanted mice were used as a model for cancer therapy in the present study. Tumor size regression was found in multiple doses of recombinant adenovirus treated mice but no regression was found in control mice. Partial tumor size regression was observed in mice treated with 1 dose of ADV-VP2. Complete regression of tumor mass was observed in 5 out of 6 mice and 2 out of 6 mice treated with 3 and 2 doses of ADV-VP2, respectively. Combined treatment of ADV-VP2 and ADV-endo demonstrated prolong mice survival time for up to one month as compared to control mice. Female mice can survive 15 days longer than male mice which suffered from similar large tumor mass. Mouse organs of recombinant adenovirus treated groups were comparable to the control group due to the nature of adenovirus which transiently expressed. The gene expression level in mouse intestines were significantly higher than other organs, 93.06±1.82 fold in 3 doses ADV-VP2 treated mice. Findings collectively justified the ability of ADV-VP2 to induce apoptosis effectively in tumor mass upon booster administration. In conclusion, the combined administration of recombinant adenovirus (ADV-VP2 and ADV-endo) had therapeutic potential against cancer. Further investigation on the optimal dosage of combined therapy need to be carried out in order to achieve the augmentative effect of these constructs on cancer therapy.